Reflections on the Context of Near-Death Experiences - Nahm, Michael (Journal of Scientific Exploration, 2011)
Near-death experiences (NDEs) constitute a particular type of experience that occurs in near-death states and is familiar to many. Yet, there are other kinds of lesser-known experiences reported from near-death states that appear to form an interconnected continuum with NDEs. Because the relations between these different experiences have not received much attention in the more recent literature, this paper presents an introductory overview on them. The topics discussed include cases of unexplained body changes during near-death states, reciprocally confirmed out-of-body experiences and crisis apparitions, deathbed visions, (shared) NDEs and (shared) dreams, correspondences between the contents of NDEs, cases of the reincarnation type, and communications received via mediums; mists or shapes leaving the body of the dying, unexplained music heard at deathbeds, the re-emergence of mental clarity shortly before death in persons with mental disorders, and unusual memories of little children. Keywords: Near-death experiences (NDEs)—deathbed visions (DBVs)—cases of the reincarnation type (CORTs)—apparitions—terminal lucidity—mediumship